2012
DOI: 10.4236/ojim.2012.22020
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of Crohn’s Disease: Latest concepts in etiology

Abstract: The notion that Crohn's Disease (CD) occurs as a result of an aberrant reaction to the commensal microbiota in genetically susceptible hosts is widely regarded by physicians and scientists as fact. Yet although it is undisputed that Crohn's Disease is immune-mediated, an aberrant reaction to one's own native flora is far from proven. The aim of the current review is to present a summary of the known infectious causes of Crohn's Disease, whilst highlighting the limitations of using outdated methods to attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…CD was described by the Scottish surgeon, TK Dalziel in 1913 [1], though it was probably described even earlier by a Polish surgeon Antoni Leśniowski in 1904 [1]. Subsequently CD was labeled as 'regional ileitis' by an American gastroenterologist, Burril Crohn [1] and so it became known as CD.…”
Section: Historymentioning
confidence: 96%
See 1 more Smart Citation
“…CD was described by the Scottish surgeon, TK Dalziel in 1913 [1], though it was probably described even earlier by a Polish surgeon Antoni Leśniowski in 1904 [1]. Subsequently CD was labeled as 'regional ileitis' by an American gastroenterologist, Burril Crohn [1] and so it became known as CD.…”
Section: Historymentioning
confidence: 96%
“…Subsequently CD was labeled as 'regional ileitis' by an American gastroenterologist, Burril Crohn [1] and so it became known as CD. Dr Burril Crohn commented initially upon its similarities to known mycobacterial infections of the gut, such as Mycobacterium tuberculosis, particularly in that it was of a 'granulomatous enteritis' nature.…”
Section: Historymentioning
confidence: 99%
“…Although it is plausible that several pathogens cause CD-like pathology, 11 Prantera 2 suggested "variable disease locations and severity" disprove a single pathogen etiology. Yet a number of pathogens cause "variable disease locations and severity."…”
Section: Variable Disease Characteristicsmentioning
confidence: 98%
“…Several independent studies, using different methods, reported an increased presence (from 25% to 55%) of mucosa-associated AIEC in CD patients [21][22][23]. AIEC was also recovered from 65% of chronic lesions and nearly 100% of biopsies from early lesions of CD patients [16].…”
Section: Introductionmentioning
confidence: 98%